Revisiting and refining the comparison of conventional and islamic markets' performance. Issue 38 (15th August 2021) - Liu, Wei-Han; Chang, Jow-Ran
ABSTRACT: With a refined version of almost stochastic dominance (ASD), we explore the performance-comparison issues between traditional markets and Islamic markets in terms of industry and business condition. The empirical outcomes indicate that Shariah compliance makes both the consumer services and finance industries in Islamic markets outshine other industries and outperform the corresponding industries in traditional markets. Except for the period before the Global Financial Crisis (GFC) in 2008, Islamic markets prevail over traditional markets in bearish (2007–2012) and persistently bullish (2013–2017) periods. These contrasts indicate that Islamic markets have emerged as a superior investment alternative since the GFC.